A benthic light index of water quality in the Great Barrier Reef, Australia. (August 2021) - Canto, Marites M.; Fabricius, Katharina E.; Logan, Murray; Lewis, Stephen; McKinna, Lachlan I.W.; Robson, Barbara J.
Abstract: Good water quality is essential to the health of marine ecosystems, yet current metrics used to track water quality in the Great Barrier Reef are not strongly tied to ecological outcomes. There is a need for a better water quality index (WQI). Benthic irradiance, the amount of light reaching the seafloor, is critical for coral and seagrass health and is strongly affected by water quality. It therefore represents a strong candidate for use as a water quality indicator. Here, we introduce a new index based on remote sensing benthic light (bPAR) from ocean color. Resulting bPAR index timeseries, based on the extent to which the observed bPAR fell short of the locally- and seasonally-specific optimum, showed strong spatial and temporal variability, which was consistent with the dynamics that govern changes in water clarity in the Great Barrier Reef. Our new index is ecologically relevant, responsive to changes in light availability and provides a robust metric that may complement current Great Barrier Reef water quality metrics.